Sport, social development and peace - Young, Kevin, 1959-; Okada, Chiaki, 1948- (Emerald, 2014)
This volume is part of the early systematic inquiry into the analysis of sport as a developmental device. The book features an international roster of global experts. The chapters represent three groups: theory and philosophy, empirical research in on-the-ground case studies, and those using circumspection to construct cases regarding evaluation.
Keywords: Sports & Recreation -- Sociology of Sports.; Sociology: sport & leisure.; Sociology.; Sports -- Sociological aspects.; elektronické knihy; electronic books